2005
DOI: 10.1007/s10865-005-2560-1
|View full text |Cite
|
Sign up to set email alerts
|

Health Events and the Smoking Cessation of Middle Aged Americans

Abstract: This study investigates the effect of serious health events including new diagnoses of heart attacks, strokes, cancers, chronic lung disease, chronic heart failure, diabetes, and heart disease on future smoking status up to six years post event. Data come from the Health and Retirement Study, a nationally representative longitudinal survey of Americans aged 51-61 in 1991, followed every 2 years from 1992 to 1998. Smoking status is evaluated at each of three followups, (1994, 1996, and 1998) as a function of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 32 publications
(31 reference statements)
2
45
1
Order By: Relevance
“…Male smokers with shorter TL may have been more likely to quit because short TL was correlated with poorer health among men in the HRS; furthermore, previous studies from the HRS showed that smokers who experience acute and chronic health events are more likely to quit smoking than are individuals who do not (37,38). This may be an example of the "healthy smoker" phenomenon, in which individuals who are more resistant to the adverse effects of smoking continue to smoke, whereas those who are more susceptible quit, resulting in underestimation of the effect of smoking (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male smokers with shorter TL may have been more likely to quit because short TL was correlated with poorer health among men in the HRS; furthermore, previous studies from the HRS showed that smokers who experience acute and chronic health events are more likely to quit smoking than are individuals who do not (37,38). This may be an example of the "healthy smoker" phenomenon, in which individuals who are more resistant to the adverse effects of smoking continue to smoke, whereas those who are more susceptible quit, resulting in underestimation of the effect of smoking (39).…”
Section: Discussionmentioning
confidence: 99%
“…This may be an example of the "healthy smoker" phenomenon, in which individuals who are more resistant to the adverse effects of smoking continue to smoke, whereas those who are more susceptible quit, resulting in underestimation of the effect of smoking (39). This adverse health-driven smoking cessation may be particularly relevant to men in the HRS, because they are more likely to experience major and chronic health events (37), and to older individuals, who are more likely than younger individuals to experience adverse health events and to quit smoking in response (40). Recent smoking cessation after entering study as a smoker a The percentage of missing data among subjects with telomere length measurement was <1% (31 of 5,554) for wave 9 smoking status, 1% (8 of 724) for wave 9 smoking rate, 15% (366 of 2,414) for years since smoking cessation, 18% (565 of 3,138) for smoking duration, and 2% (28 of 1,243) for "on-study" pack-years.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reports of new disease diagnoses by physicians are also included in the model. Several of these have been found to increase use of clinical services (Wu 2003) and to encourage healthier behavior, such as quitting smoking (Falba 2005). Diagnoses by physicians also have the advantage of being somewhat more objective measures of health status.…”
Section: Methodsmentioning
confidence: 99%
“…While the FE models are able to address biases due to time-invariant unobserved factors, they do not account for time-varying unobserved variables affecting both smoking and cognition. Particularly in the case of older individuals, events such as health shocks or decreased labor force participation are common and such events have been shown to affect both smoking and cognition (Falba, 2005;Khwaja et al, 2006;Keenan, 2009;Savva and Stephan, 2010). To account for such time varying factors, we re-estimate the FE models adding extensive controls for health, income and retirement status (see Table 6).…”
Section: Resultsmentioning
confidence: 99%